Maintaining Your Marketing Competitiveness Through Marketing Innovations - Church, Nancy J. (Mercados y Negocios, 2024)
A revolution is occurring in marketing today due to the application of artificial intelligence (AI) to various marketing tasks and functions. In addition, marketing innovations are taking place on Web 3.0, in the Metaverse, in virtual and augmented reality, in omnichannel marketing, in social media, in video marketing, in live streaming, in connected and addressable TV, in voice and visual search, in influencer marketing, in how advertising budgets are allocated, in social shopping, and additional credentials for marketing professionals in a dynamic profession. Marketing professionals and marketing professors must prioritize pursuing continuous education in their field due to the dynamic nature and complex changes in marketing technology and media options.